Antibacterial and anticandidal activity of Tylosema esculentum (marama) extracts - Walter Chingwaru; Gyebi Duodu; Yolandi van Zyl; C.J. Schoeman; Runner Majinda; Sam Yeboah; Jose Jackson; Petrina Kapewangolo; Martha Kandawa-Schulz; Amanda Minnaar; Avrelija Cencic (South African Journal of Science, 2011)
Bean and tuber extracts of Tylosema esculentum (marama) - an African creeping plant - were obtained using ethanol, methanol and water. Based on information that T. esculentum is used traditionally for the treatment of various diseases, the antibacterial and anticandidal effects of tuber and bean extracts were investigated. The antimicrobial activity of the extracts was tested on methicillin-resistant Staphylococcus aureus (MRSA, ATCC 6538), Mycobacterium terrae (ATCC 15755), Corynebacterium diphtheriae (clinical) and Candida albicans (ATCC 2091). We performed the broth microdilution test for the determination of the minimum inhibitory concentration (MIC) and a method to determine survival of microorganisms after in vitro co-incubation with the highest concentrations of T. esculentum extracts, followed by assessment of colony counts. Ethanol and methanol (phenolic) bean extracts exhibited higher potency against bacteria and yeast than aqueous extracts. Marama bean seed coat crude ethanolic extract (MSCE) and seed coat polyphenolic fractions, especially soluble-bound fraction (MSCIB), were highly antimicrobial against M. terrae, C. diphtheriae and C. albicans. All marama bean polyphenolic fractions, namely cotyledon acidified methanol fraction (MCAM), seed coat acidified methanol fraction (MSCAM), cotyledon insoluble-bound fraction (MCIB), seed coat insoluble-bound fraction (MSCIB), cotyledon-free polyphenolic fraction (MCFP) and seed coat free polyphenolic fraction (MSCFP) had high antimicrobial effects as shown by low respective MIC values between 0.1 mg/mL and 1 mg/mL. These MIC values were comparable to those of control antimicrobials used: amphotericin B (0.5 mg/mL) and cesfulodin (0.1 mg/mL) against C. diphtheriae, streptomycin (1.0 mg/mL) and gentamicin (0.4 mg/mL) against M. terrae, and amphotericin B (0.05 mg/mL) against C. albicans. Marama seed coat soluble-esterified fraction (MSCS) had closer activity to that of cefsulodin against M. terrae. High amounts of phenolic substances, such as gallic acid, especially in the seed coats, as well as high amounts of phytosterols, lignans, certain fatty acids and peptides (specifically protease inhibitors) in the cotyledons contributed to the observed antibacterial and anticandidal activities. Marama extracts, especially phenolic and crude seed coat extracts, had high multi-species antibacterial and anticandidal activities at concentrations comparable to that of some conventional drugs; these extracts have potential use as microbicides.